Body composition, metabolic profile and fitness in older versus younger type 2 diabetic participants to six months of aerobic exercise, resistance exercise or combined aerobic and resistance exercise. - Dittmann, Katherine R. (University of Ottawa (Canada), 2004)
In previous research, resistance exercise reduced HbA1c primarily in studies of older type 2 diabetic (T2DM) subjects (age>55), while aerobic exercise reduced HbA1c primarily in studies of relatively younger subjects. We compared changes in HbA1c, fitness and body composition in response to 6 months of exercise training in older (55-70 yrs: n= 53) vs. younger (40-54 yrs: n=44) T2DM participants in a randomized trial. Previously inactive T2DM subjects were randomized to aerobic exercise (A; progressing to 45min at 75% HR max, n=24), resistance exercise (R; 2-3 sets of 8-12 RM, n=23), combination aerobic and resistance training (AR; n=25) or a waiting control-list group (C; n=25). Each exercise group trained 3x/wk for 6 months. Strength testing was done using an 8 repetition maximum (RM) protocol for seated row, leg press and bench press. V02peak was assessed using graded treadmill protocols to volitional fatigue. A single cut CT scan was used to quantitate abdominal visceral and subcutaneous fat and mid-thigh muscle cross-section. All tests were performed at baseline and 6-months. The responses of older and younger subjects did not differ significantly on any measure. A1c decreased from 8.0% to 7.1% in younger A, and from 7.4% to 6.7% in older A. In AR decreases were similar: 7.9% to 6.8% in younger AR, 7.8% to 6.8% in older AR. A1c changed little in R: 7.8% to 7.7% in younger R, 7.7 to 7.3% in older R. No significant change in HbA1c occurred in either older or younger subjects in C. Mean increases in VO2peak for A were 6.9% in old and 7.4% in young and for AR were 7.6% in old and 4.9% in young. Strength increased in AR by 47.5%, 51.0% and 37.9% in young and 41.1%, 46.0% and 30.4% in young for bench press, leg press and seated row respectively. The R young group improved by 68.6%, 86.2% and 47.6% and the old by 44.3%, 72.3% and 31.9% for bench press, leg press and seated row respectively. The aerobic only group also improved in strength. Neither VO2peak nor strength changed significantly in C. Therefore, older (55-70 years old) and younger (40-54 year old) T2DM subjects responded similarly to aerobic, resistance or combined exercise in terms of glycemic control, strength, and aerobic fitness.
Keywords: Health Sciences, Recreation.